Association of Maternal Creatinine-to-Body Weight and Urea-to-Creatinine Ratios with Gestational Diabetes Mellitus - Ayas Özkan, Merve; Dayanan, Ruken; Duygulu Bulan, Dilara; Özkan, Halis Doğukan; Aktemur, Gizem; Karabay, Gülşan; Tokgöz Çakır, Betül; Şeyhanlı, Zeynep; Atılgan Yıldırım, Ayşegül; Akın, Furkan; Vural Yılmaz, Zehra (The European Research Journal, 2026)
Objectives: Gestational diabetes mellitus (GDM) is a multifactorial metabolic disorder associated with altered glucose metabolism and systemic physiological adaptations during pregnancy. Subtle changes in renal-related biochemical parameters may reflect underlying metabolic alterations accompanying GDM. This study aimed to evaluate the association between maternal creatinine-to-body weight (Cre/BW) and urea-to-creatinine (Urea/Cre) ratios and GDM, with a particular focus on their potential role as renal–metabolic indicators during pregnancy. Methods: This retrospective case–control study included 1,064 pregnant women (532 with GDM and 532 matched controls) who underwent a 75 g oral glucose tolerance test between 24 and 28 weeks of gestation. Propensity score matching was applied to reduce baseline differences between groups. Maternal serum creatinine, urea, and body weight were recorded in the first and second trimesters, and Cre/BW and Urea/Cre ratios were calculated. Group comparisons, receiver operating characteristic (ROC) analyses, and multivariate logistic regression were performed. Results: In the second trimester, the Cre/BW ratio was significantly lower, and the Urea/Cre ratio was significantly higher in women with GDM compared with controls (both P